Student Perspectives on State Universities in Surabaya - Noerhartati, Endang; Sahid Budiharseno, Rianmahardhika (Universitas Islam Sultan Agung, 2024)
In this digital era, online reviews are an important factor influencing prospective students' decisions in choosing a university. This research focuses on the influence of online reviews on students' perceptions of state universities in Surabaya. Using quantitative and qualitative approaches, this study explores the level of student satisfaction and its impact on their decision in choosing a university. The research results show that online reviews, as a form of digital word-of-mouth, have a significant role in providing honest and unfiltered insight into campus life, facilities, instructors, and other aspects. This research also found that students use online reviews as one of the main sources of information before making online purchases through the marketplace. With increasing internet access, students have become more informed and selective, relying not only on academic reputation but also on real-world experiences shared by other students. This study suggests universities in Surabaya to be proactive in managing online reviews to ensure a positive and accurate image of their institutions, which can ultimately increase their attractiveness to prospective new students.